A SYSTEMATIC REVIEW OF COST OF CAPITAL AND SUSTAINABILITY PERFORMANCE - Widiyanti, Novi Wulandari; Zakiya, Annisa Luthfi; Pratiwi, Ratna Ika Putri; Putri, Riska Bunga Rosmalia (Jurnal Ilmiah Akuntansi Indonesia, 2024)
Abstract: This research aims to comprehensively identify theoretical analysis and provide concrete empirical presentations relating to research trends regarding capital cost variables over the last five years from the top ten studies. The increasing popularity of investing among the public and the need for companies to plan new projects or expand product lines strategically have led to this crucial investigation. Focusing on the cost of capital, especially the weighted average cost of capital (WACC), is critical because it significantly impacts a business's growth strategy and various financial decisions. The profound impact of the cost of capital on business decisions cannot be overstated. This paper is a literature review, with qualitative analysis methods and data collection techniques through extensive reviews. This comprehensive review resulted in several studies in which the cost of capital (WACC) across various sectors and contexts highlights its impact on ownership structure and ESG practices. So, the cost of capital is a key determining factor in various financial decisions, with factors such as high-quality ESG reporting and ownership structure significantly impacting costs